Development of cereal bar using dehydrated brassage pomace and incorporation of hydrolyzed soy protein and gelatin (Research, Society and Development, 2022)
The brassage pomace is the by-product generated in greater amounts during beer processing. This residue has a high content of proteins, minerals, dietary fiber, and water content. Drying processes allow for an increase in the shelf life of the brassage pomace and its application in food products. Among these products, cereal bars have excellent potential, as they are expanding widely in the market and are an easy-to-handle food matrix. In addition to the increase in dietary fiber content, the incorporation of proteins improves the nutritional profile of cereal bars. Thus, we aim to carry out the drying process of the brassage pomace at three temperatures (40, 60 and 80 ºC) and apply it to cereal bars with hydrolyzed soy protein and gelatin. The Response Surface Methodology was used as an experimental strategy through a Central Composite Rotational Design of three independent variables. The evaluated responses were instrumental color and texture, bulk density, water activity and moisture. The optimal point (P < 0.10 and R2 > 0.80) was defined using 27.08 % brassage pomace, 12.44 % hydrolyzed soy protein and 0.89 % hydrated gelatin (1:3 – gelatin:water ratio). It was observed that the optimized point presented satisfactory technological characteristics, with a significant reduction in the levels of lipids, sugars and starch and an increase in the levels of proteins, minerals and dietary fiber. In addition, the optimized point showed a 19.27 % reduction in the total caloric value.